Computational exploration of wave propagation and heating from transcranial focused ultrasound for neuromodulation. (28th July 2016) - Mueller, Jerel K; Ai, Leo; Bansal, Priya; Legon, Wynn
Abstract: Objective. While ultrasound is largely established for use in diagnostic imaging, its application for neuromodulation is relatively new and crudely understood. The objective of the present study was to investigate the effects of tissue properties and geometry on the wave propagation and heating in the context of transcranial neuromodulation. Approach. A computational model of transcranial-focused ultrasound was constructed and validated against empirical data. The models were then incrementally extended to investigate a number of issues related to the use of ultrasound for neuromodulation, including the effect on wave propagation of variations in geometry of skull and gyral anatomy as well as the effect of multiple tissue and media layers, including scalp, skull, CSF, and gray/white matter. In addition, a sensitivity analysis was run to characterize the influence of acoustic properties of intracranial tissues. Finally, the heating associated with ultrasonic stimulation waveforms designed for neuromodulation was modeled. Main results. The wave propagation of a transcranially focused ultrasound beam is significantly influenced by the cranial domain. The half maximum acoustic beam intensity profiles are insensitive overall to small changes in material properties, though the inclusion of sulci in models results in greater peak intensity values compared to a model without sulci (1%–30% greater). Finally, heating using currently employed stimulation parameters in humans is highest in bone (0.16 °C) and is negligible in brain (4.27 × 10 –3 °C) for a 0.5 s exposure. Significance. Ultrasound for noninvasive neuromodulation holds great promise and appeal for its non-invasiveness, high spatial resolution and deep focal lengths. Here we show gross brain anatomy and biological material properties to have limited effect on ultrasound wave propagation and to result in safe heating levels in the skull and brain.